How Emotional Intelligence and Entrepreneurial Mindset Drive Organizational Performance: The Moderating Effect of Reward - Juliandri Hasnur; Syahrizal Syahrizal; Rino Rino (Universitas Muhammadiyah Jakarta, 2026)
Recent studies have yielded ambiguous results about the influence of emotional intelligence and an entrepreneurial mindset on organisational success, especially in vocational higher education institutions where reward systems might affect employee behaviour. This study examines the impact of emotional intelligence and entrepreneurial mindset on organisational success, with rewards serving as a moderating variable in the context of vocational marine higher education. The sample comprised 330 employees from Politeknik Pelayaran Sumatera Barat and Politeknik Ilmu Pelayaran Semarang. The data analysis utilised PLS-SEM with SmartPLS 3, employing bootstrapping and blindfolding methodologies. The findings demonstrate that an entrepreneurial mentality exerts a favourable and significant effect on organisational performance, whilst emotional intelligence also enhances performance, albeit without statistical significance. Rewards have a strong and direct effect on how well an organization does its job, but they don't change the relationship between emotional intelligence and how well an organization does its job, or between an entrepreneurial attitude and how well an organization does its job. The model explains a large part of the differences in how well organisations do and shows that it can accurately forecast how well they will do. This study adds to the body of research by making the roles of emotional intelligence, an entrepreneurial attitude, and rewards in creating organisational success on vocational marine campuses clearer. It also shows how important institutional reward systems are in this setting.